Smart Fish Feeder Using Solar Energy - Shahiran, Mohammad Danial; Salimin, Suriana (Journal of Electronic Voltage and Application, 2021)
Smart fish feeder is an emerging concept of the current trend which use Internet of Things (IoT) technology to operate, monitoring and provides crucial information and status to the whole farming system. This project aims to provide such essential proof of concept that utilized IoT technology combine with the solar energy to power up servo motor and temperature sensor that connect from NodeMCU for the agriculture system. The main objectives of this project are specifically focused on the development of a smart fish feeder by using solar system with charging capability and controlled by the IoT system. Such a fish feeder system was powered up by 12V battery using 10W solar panel controlled by solar charger controller. The solar energy was stored to 12 V rechargeable battery. IoT controlled sensors were also attached to the fish feeder system for providing essential information on temperature and fish feeder timer via the Blynk platform. The results of the developed system successfully proved the concept is workable and could be extended to a larger scale of the farming industry. Owing to its energy autonomy and low cost, the system has the potential to be useful in smart farming technology.